Perspectives of physical therapists regarding the use and value of screening assessments and preventative programs for elite-level dancers - Kilburn, C.M.; Singh, H.; Makowski, A.; Musselman, K. (Journal of Dance Medicine & Science, 2020)
Inconsistency exists in research findings regarding the use and efficacy of screening assessments for elite-level dancers. The purpose of this study was to gain an understanding of physical therapists` perspectives on the use and value of screening assessments and preventative measures in this population in order to inform future research and clinical care. Semi-structured interviews were conducted with nine physical therapists with a caseload of at least 25% dancers aged > 14 years and enrolled in a professional or pre-professional program (i.e., elite-level dancers). Transcribed interviews were analyzed using an Interpretive Description framework. A constant comparative analysis was used to identify similarities and differences among and within the data. Themes and categories were finalized after consensus among research team members. Resulting themes included the values, challenges, barriers, and opportunities of screening and preventative programs. Values extended beyond injury prevention to such matters as performance optimization, development of rapport, communication, and education. Challenges included a lack of research and support from dancers, artistic staff, and the traditional dance culture. Opportunities were seen for improved standardization and innovation of screening procedures. Recommendations to guide clinical practice and research represent an initial step toward improving implementation of screening and preventative programs, which may provide benefits to dancers` health and performance.